Correlation between Urinary Albumin to Creatinine Ratio and In-hospital Cardiac Events among Patients with Acute Myocardial Infarction (Cardiovascular Journal, 2016)
Background: Urinary albumin to creatinine ratio (UACR) is an important predictor of major adverse cardiac events (MACE). However, limited data is available regarding its correlation with in-hospital MACE in patients with acute myocardial infarction (AMI). The aim of the current study was to find out the correlation between UACR and in-hospital MACE among patients with AMI.Methods: 651 AMI patients (mean age: 54.4 ± 12.6 years, male/female: 522/129, STEMI/NSTEMI: 438/213) admitted from November 2013 to December 2014 were enrolled in this observational study. The UACR was measured from spot urine samples collected on admission day. Data on patients demography, existence of traditional risk factors for cardiovascular diseases (CVD) and baseline clinical parameters were recorded on admission day. The patients were categorized into three groups - normoalbuminuria (UACR less than 30mg/gCr, n = 404), microalbuminuria (UACR between 30 to 299 mg/gCr, n = 215) and macroalbuminuria (UACR equal to or greater than 300 mg/ gCr, n = 32). For each enrolled patients, the incidences of specified in-hospital MACE (recurrent angina, acute heart failure, arrhythmia, atrio-ventricular conduction disorders, mechanical complications, cardiogenic shock and cardiac arrest) were recorded throughout the hospital staying period. The comparison of categorical variables between the groups was performed using the chisquare test. p < 0.05 was considered statistically significant.Results: The baseline characteristics (age, male gender, hypertension, hyperlipidemia, diabetes mellitus, family history of CVD, smoking) of three groups were statistically similar. Compared to normoalbuminuria group, the incidences of MACE were significantly higher in micro and macro albuminuria group (p-value: normo vs. micro 0.001 and normo vs. macro 0.006). However, the occurrences of MACE in microalbuminuria group were statistically similar to those of macroalbuminuria group (p-value: micro vs. macro 0.284).Conclusion: Urinary albumin to creatinine ratio, at a level of micro and macro albuminuria, was associated with greater incidence of in-hospital MACE compared to its normal level in patients with AMI.Cardiovasc. j. 2016; 8(2): 90-93